PENGARUH UKURAN PERUSAHAAN DAN PAJAK TERHADAP TRANSFER PRICING (Jurnal Riset Akuntansi, 2022)
Transfer pricing has become a global problem that can also occur in Indonesia. Multinational companies with many entities in various countries with different tax rate policies can encourage transfer pricing. The influence of the central company which is very dominant in the management policies of its entity companies through special relationships is the key to transfer pricing, especially in manufacturing companies. This study aims to analyze the impact of company size and tax on transfer pricing in 12 (twelve) registered automotive and component manufacturing sub-sector companies in 2018-2020. The analysis technique tested the hypothesis with logistic regression, interaction test and logistic regression significance test to determine the probability. The results show that company size and taxes have a negative impact on transfer pricing. Keywords: company size, tax, transfer pricing